Analysis of Floating lift net catches Based on Catch Per Unit Effort in Kolono Bay - Angraeni, Resky Dwi Angraeni Dwi; Alimina, Naslina; Tadjuddah, Muslim (Grouper, 2023)
Kolono Bay waters are one of the waters in South Konawe Regency which has a large potential for fishery resources. One of the leading commodities in the waters of Kolono Bay is anchovy. Fishing activities in the waters of Kolono Bay still use the traditional fishing gear. The purpose of this study was to determine the number of catches based on catch per unit effort (CPUE) using a floating lift net. This research was carried out for three months from January - March 2019 in the waters of Kolono Bay, South Konawe Regency, Southeast Sulawesi Province. The collection location consisted of 10 observations which were determined based on the existence of floating charts scattered in the areas of Lambangi Village and Puupi Village. Stations are set to represent the existence of charts in Kolono Bay. Time series data of catches, and the position of fishing areas are obtained through activities in the field with the help of GPS. The catches obtained were analyzed descriptively and presented in the form of tables and graphs. The catches obtained from each research sample were combined to analyze the average number of catches per station and the average number of catches per month then the catch was calculated for CPUE per station. The CPUE value is obtained from the comparison of catches with the number of trip charts. The results showed at station 5 the highest catches with an average CPUE value of 24.33 kg per hauling per month of catching close to the coast. Therefore, in the context of efficiency and optimization of results, it is recommended to place and operate charts around coastal waters.